The Relationship between Physical Activity Variety and Objectively Measured Moderate-to-Vigorous Physical Activity Levels in Weight Loss Maintainers and Normal-Weight Individuals - Dale S. Bond; Hollie A. Raynor; Suzanne Phelan; Jeremy Steeves; Richard Daniello; Rena R. Wing (Hindawi Limited, 2012)
Given the importance of physical activity (PA) for weight control, identifying strategies to achieve higher PA levels is imperative. We hypothesized that performing a greater variety of self-reported moderate-to-vigorous activities (MVPAs) would relate to higher objectively measured MVPA minutes in two groups who were successfully maintaining their body weight: weight loss maintainers (WLM/n=226) and normal-weight individuals (NW/n=169). The Paffenbarger Questionnaire and RT3 accelerometer were used to determine variety/number of different MVPAs performed and MVPA minutes, respectively. The variety/number of different activities performed by WLM and NW was similar (1.8 ± 1.2 versus 1.7 ± 1.2, P=0.52). Regression analyses showed that greater variety (P<0.01) and WLM status (P<0.05) were each positively related to greater MVPA minutes/day and meeting the ≥250 MVPA minutes/week guideline for long-term weight maintenance. The association between greater variety and higher MVPA was similar in NW and WLM. Future studies should test whether variety can facilitate engagement in higher MVPA levels for more effective weight control.